What can reaction databases teach us about Buchwald–Hartwig cross-couplings?. Issue 48 (1st November 2020) - Fitzner, Martin; Wuitschik, Georg; Koller, Raffael J.; Adam, Jean-Michel; Schindler, Torsten; Reymond, Jean-Louis
Abstract : An analysis of the entire literature on Pd-catalyzed C–N couplings enables data-driven insight and provides recommendations for reaction conditions. Abstract : Despite the widespread and increasing usage of Pd-catalyzed C–N cross couplings, finding good conditions for these reactions can be challenging. Practitioners mostly rely on few methodology studies or anecdotal experience. This is surprising, since the advent of data-driven experimentation and the large amount of knowledge in databases allow for data-driven insight. In this work, we address this by analyzing more than 62 000 Buchwald–Hartwig couplings gathered from CAS, Reaxys and the USPTO. Our meta-analysis of the reaction performance generates data-driven cheatsheets for reaction condition recommendation. It also provides an interactive tool to find rarer ligands with optimal performance regarding user-selected substrate properties. With this we give practitioners promising starting points. Furthermore, we study bias and diversity in the literature and summarize the current state of the reaction data, including its pitfalls. Hence, this work will also be useful for future data-driven developments such as the optimization of reaction conditions via machine learning.